1989
DOI: 10.1007/bf01743989
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic long-term results after cervical vertebral interbody fusion with Polymethyl Methacrylat (PMMA)

Abstract: Long-term results of cervical interbody fusion with PMMA were evaluated in a retrospective study. X-ray films of 83 patients were obtainable. Post-operative follow-up in this series was between 15 and 20 years. The results show that PMMA is engrafted after about 2 years. Stable vertebral interbody fusion is obtained in about 90% of cases. Development of malignoma was not observed. Resorptive bone alterations, which can be seen in about 2% of cases one to two years after operation are shown not to be progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 8 publications
(7 reference statements)
0
27
0
Order By: Relevance
“…Hamburger et al investigated the clinical long-term significance of reduced osseous union in PMMA interbody fusions, and found 77.5% of 249 patients reported successful outcomes after a minimum 10-year follow-up [41]. However, fusion with PMMA has been reported to occur 15-20 years postoperatively in 90% of cases [17]. Necrosis of adjacent vertebrae and limited ventral ossification were also noted [17].…”
Section: Polymethylmethacrylate (Pmma)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hamburger et al investigated the clinical long-term significance of reduced osseous union in PMMA interbody fusions, and found 77.5% of 249 patients reported successful outcomes after a minimum 10-year follow-up [41]. However, fusion with PMMA has been reported to occur 15-20 years postoperatively in 90% of cases [17]. Necrosis of adjacent vertebrae and limited ventral ossification were also noted [17].…”
Section: Polymethylmethacrylate (Pmma)mentioning
confidence: 99%
“…However, fusion with PMMA has been reported to occur 15-20 years postoperatively in 90% of cases [17]. Necrosis of adjacent vertebrae and limited ventral ossification were also noted [17]. Some authors have investigated the modification of PMMA into a cage structure filled with autologous cancellous bone, reporting successful fusion rates with limited donor site morbidity [24,67].…”
Section: Polymethylmethacrylate (Pmma)mentioning
confidence: 99%
“…The use of polymethyl methacrylate (Pala-cos) as an interbody graft is still a widespread and popular method. It is easy to handle, cheap and gives good results [3,5,13,14]. However, it has been shown that tight fusion does not take place, but only tissue consolidation that still allows movement in the "fused" segment [3,5,16].…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to handle, cheap and gives good results [3,5,13,14]. However, it has been shown that tight fusion does not take place, but only tissue consolidation that still allows movement in the "fused" segment [3,5,16]. This may be seen to be favourable from a physiological point of view, but does not comply with the intention of a segmental fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation